Targeting Clever-1 to Overcome Therapy Resistance in Myeloid Malignancies - Mickos, Jesper (My University, 2024)
Acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) are myeloid malignancies. These life-threatening diseases are caused by aberrant proliferation of malignant cells and disruption of normal hematopoiesis needed to form a functioning immune system. Moreover, these diseases are characterized by very poor survival rates. While treatment options have improved, the majority of patients relapse, and these diseases are fatal to most patients due to resistance to standard-of-care treatments. New treatments capable of overcoming resistance to current treatments are in dire need, and two encouraging strategies are targeting the disease through metabolic weaknesses or the immune system. Bexmarilimab, an anti-Clever-1 antibody has the potential to treat myeloid malignancies through both the metabolic and immunotherapeutic routes and is currently under clinical investigation in combination with current standard therapies to treat patients with AML and MDS. This work aimed to elucidate the mechanism behind bexmarilimab-induced suppression of mitochondrial metabolism and the role of Clever-1 in therapy resistance and stemness. AML cell lines were characterized for expression of Clever-1 and stemness markers with flow cytometry. Additionally, the abundance of key metabolites following bexmarilimab treatment was measured to investigate bexmarilimab’s mode of action. The cell lines that respond to bexmarilimab were found to have a higher abundance of glutathione, suggesting the involvement of glutathione metabolism in bexmarilimab response. Moreover, the results indicate that venetoclax treatment increases the plasma membrane expression of Clever-1, indicating possible synergism of these two therapies. These results guide subsequent investigation into bexmarilimab’s mechanism of action, which is crucial to explain the clinical benefits observed in patients.
Keywords: acute myeloid leukemia, myelodysplastic syndrome, drug resistance, metabolism, Clever-1, bexmarilimab